الأشراف الأداري وتطويره بوزارة التربية والتعليم في سلطنة عمان في العصر الحاضر - Sultan Bin Saleh Bin Muhammed Al-Balushi
This research aims to develop the administrative supervision of the Ministry of Education in the Sultanate of Oman, assuming the researcher that there are many reasons calling for the development, and the need for a supervision system of the comprehensive management, most notably that the era of scientific and technological revolution and the explosion of knowledge and international cooperation in which we live requires us to benefit from the experiences others, which requires the provision of sophisticated quality of supervision that will monitoring the activeness and seriousness of the administrative role. The approach taken in this research is descriptive method which is based on the description of the nature of the administrative supervision of the Ministry of Education in the Sultanate of Oman,where supervision is also used in analyzing the system study approach to identify the components of the supervisory process. Among the arguments and evidence presented to clarify and strengthen the objectives of the research are: the Orbiter to averse the administrative Ministry of Education in Oman with the succession movements,change it and change from unnamed inspection based on surprise and nitpick guidance and also through human relations. This study differs from other previous studies in terms of the novelty of the theme, and in terms of its way of collecting, analyzing and arranging information,as well as in terms of the handling of administrative supervision and development of the Ministry of Education in the Sultanate of Oman in the present era, either directly or indirectly. The study has come out with several significant results, including: that the administrative supervisor formulate goals in an objective manner, and the inevitability of planning the training programs and the need to involve employees in the decision-making process and change the scope of the supervision of supervisors administrators administrators of school in every specific time period for the exchange of experiences and transfer of experiences distinct and improving the pattern of horizontal communication to access the pattern of interactive communication between supervisors and administrative departments of the schools and work on the use of means of communication and modern technology and the need for giving attention to the process of evaluating the performance of supervisors and administrative departments of the schools and connecting the outputs of this process as the annual incentives for them.I exited the study with perception of a full development system administrative supervision of the Ministry of Education in the Sultanate of Oman, includes justifications for its development and supporting infrastructure and objectives and strategies and the selection criteria for the administrative supervisor and competencies that must be met in it and this training and rehabilitation and its role in the operations of administrative supervision also touched on the challenges of application development development mechanisms and ways to overcome them.